Analisis Harga Pokok Produksi CPO terhadap Penentuan Harga Jual di PT. Perkebunan Nusantara IV Regional II - Nur Halisah; Tifany Zia Aznur; Dina Arfianti Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The palm oil industry is a strategic commodity that contributes significantly to Indonesia's foreign exchange. Determining the correct and competitive selling price of Crude Palm Oil (CPO) depends heavily on the accuracy of calculating the cost of goods sold (COGS). Errors in calculating COGS can result in the selling price being too low, thus causing losses to the company, or too high, thus reducing competitiveness in the market. This study aims to determine the amount of CPO production cost and the profit obtained by PT. Perkebunan Nusantara IV Regional II based on the selling price achieved in 2024. This study uses a descriptive quantitative approach with a method of collecting production costs using process costing and a method of determining COGS using full costing which includes raw material costs, direct labor costs, and fixed and variable factory overhead costs. The data used are secondary data obtained from the company's 2024 financial statements. The results show that the total production cost is IDR 2,925,998,297,226 with a total production of 661,904,862 kg of CPO, resulting in a COGS of IDR 4,420.57/kg. With an average selling price of Rp12,722,337/kg, the company's total revenue reached Rp8,420,976,716,302 and a profit of Rp5,494,978,419,076 per year. The results of this study indicate that the accurate application of the full costing method can be used as a basis for determining optimal selling prices and increasing company profitability.